Design, Synthesis, and Evaluation of Benzoheterocyclic-Containing Derivatives as Novel HDAC1 Inhibitors - Jiao, Min-Ru; Han, Bo; Gu, Xiu; Zhang, Hao; Wang, Ai-Ping; Zhang, Qing-Wei (Pharmaceutical Fronts, 2022)
In this study, the synthesis and biological evaluation of a variety of benzoheterocyclic-containing benzamide derivatives were described. Some of these compounds were proved to inhibiting the activity of histone deacetylase 1 (HDAC1) with IC50 values below the micromolar range, retarding proliferation of several human cancer cells, and surprisingly, not possessing toxicity to human normal cells and hERG K+ ion channels. Among those compounds, 3c was the most potent and efficacious derivative. Compound 3c was orally active and displayed excellent in vivo antitumor activity in a HCT-116 xenograft mice model.
Keywords: benzamide derivatives; HDAC1 inhibitors; orally active; antitumor activity